اسلامی عائلی مسائل کی وسعت اوردائرہ کار : تحقیقی وتجزیاتی مطالعہ: Scope and Framework of Islamic Family Issues: A Research and Analytical Study - Muhammad Noor; Hafiz Muhammad Kashif; Asad Lateef (Al Manhal Research Journal, 2023)
For the social life of a civilized human to be protected from mutual conflicts, law is essential, and among different sets of laws, the most delicate is family law. This is because it reforms the inner workings of the household and ensures the management of the home. Since Islam desires the formation of a successful society, and society is a collection of individuals, it is impossible to conceive of a successful society until individuals are reformed. If individuals do not have familial peace, the path to progress becomes desolate and barren. Additionally, there is a greater risk of injustice and oppression in domestic life, as on one side there is the natural weakness of the delicate gender and on the other the threat of violence from the physically stronger men. In a conflict between the two, the possibility of the stronger dominating the weaker always exists. Therefore, for the demarcation of family life, certain laws are necessary, and the legislator has fully taken care of this need. In short, the law of marriage is the most important among the laws of civilization. Family laws and commands include everything from marriage and divorce to the rights of children, relatives, family members, and the practice of kinship, etc. The human world is a collection of many individuals where each individual is active. In such a situation, it was necessary to set a limit for everyone, to establish a balance between different individuals which guarantees that an individual will complete his own being without being a problem for others. He will continue his journey without unnecessary conflicts with others. The entire foundation of the social system is based on personal law and family law. The education and upbringing of an individual, the nature of family relationships, the internal order and discipline of the home, and the formation and training of the family, i.e., the initiation of a small world, are all based on these laws, which eventually lead to the formation of a neighborhood, a city, a nation, and a country.